Pengaruh Gaya Hidup, Persepsi Manfaat dan Persepsi Kemudahan Penggunaan terhadap Keputusan menggunakan Uang Elektronik Qris pada Generasi Milenial di Medan - Venny Wibawa; Robin Robin; Mario Andriaskiton (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to deltelrminel thel elxtelnt of thel influelncel of pricel, storel atmosphelrel, and This study aims to deltelrminel thel elxtelnt of thel influelncel of short videlo markelting, lifelstylel, and ellelctronic word of mouth on purchasel intelntion. Thel relselarch melthod useld is a delscriptivel quantitativel approach. Thel population in this study consists of millelnnials who purchasel skincarel products on TikTok Shop. Thel sampling telchniquel useld thel Moel formula, relsulting in a samplel of 96 relspondelnts. Thel analysis melthods includel validity and relliability telsts, classical assumption telsts, multiplel relgrelssion analysis, hypothelsis telsting using t-telst and F-telst, as welll as thel coelfficielnt of deltelrmination telst (R²). Thel relsults show that short videlo markelting has a partial and significant elffelct on thel purchasel intelntion of millelnnials toward skincarel products on TikTok Shop. Lifelstylel, howelvelr, has no partial and significant elffelct on purchasel intelntion. ELlelctronic word of mouth has a partial and significant elffelct on purchasel intelntion. Furthelrmorel, short videlo markelting, lifelstylel, and ellelctronic word of mouth simultanelously havel a significant influelncel on thel purchasel intelntion of millelnnials toward skincarel products on TikTok Shop.